Pencacah Bobot Lengkap dari Kode Ternari - Diana Putri Prahasti; Nur Hamid (UJMC (Unisda Journal of Mathematics and Computer Science), 2025)
This paper presents the explicit forms of complete weight enumerators (CWEs) for ternary self-dual codes of lengths 4, 8, 12, 16, and 20. Complete weight enumerators polynomials describe the distribution of the symbols 0, 1, and 2 in each codeword, making them essential for analyzing non-binary codes. The results focus on the complete weight enumerators polynomials that form a basis for each code. This documentation serves as a concrete reference for further research in ternary code theory.